GRAND DESAIN SMS DALAM MBS UNTUK MEWUJUDKAN SEKOLAH YANG EFEKTIF DAN UNGGUL - Waluyo Iskak (CENDEKIA: Jurnal Studi Keislaman, 2016)
The purpose of this study is to describe the preparation, implementation and results of the grand design of SMS in MBS for consummating an effective and excellent school at SDN 3 Tambak, Tambak Subdistrict of Gresik Regency in 2015. This study was conducted in SDN 3 Tambak Tambak Subdistrict Gresik in 2015 using school profile data. The implementation of study was carried out for 3 months from August to October 2015 with the observation and documentation method. The result shows that the SMS method has improved the academic and non academic achievement of students, enthusiasm and competence of teachers, infrastructure, financial management, school management and PSM. The conclusion is that the implementation of SMS in the grand design of MBS can consummate an effectiveness and excellence school of SDN 3 Tambak Tambak District of Gresik Regency in 2015.